(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
The roles which women portray in media have been the subject of much public criticism and debate. Over the years, this topic has received serious attention in developing social status of women in the society. Mass media can be considered as a dynamic instrument to promote social and economic value for women and foster social development in urban and also less developed regions of the nation. In order to truly contribute to the status of women in the society, it is necessary for researchers and academicians to have a thorough understanding of how people react or behave after watching the roles essayed by women. Taking this into consideration, the present study aims to analyze the “Impact of Roles Portrayed by Women in Media: A Debate on Ethical or Unethical Content, A study in Gurgaon Region.” This paper reviews & describes some problem areas whose exploration will provide useful insights aimed at improving the ethical content in advertising, over-all marketing strategy and films. The present paper also identifies the effects of projected roles of women by mass media on women psychology and health and also on the image of women in the society. Portrayal of women can have both positive and negative effects on women and their image. This study will also give an insight on the impact of various variables such as crime against women, repeated exposure of sexy roles, reverse gender roles, portrayal of lean, attractive and decorative body of women etc. on the behavior and psychology of men and women, especially young girls and boys in the society. The responsibility of filmmakers, advertisers, marketers, scriptwriters, story writers, directors and producers, actors etc. becomes imperative in developing ethical content for the growth of humanity in the world. The focus will be also on the role of mass media and its impact on public in various campaigns and court cases such as Femina’s Campaign, - “Raising The Bar”, Jessica Lal Murder, Arushi Murder and Nirbhaya Case. The need is to enrich the idea of change and development in the society while developing meaningful and ethical content through mass media.